The Difference Secretory Immunoglobulin A between Faeces Sample of Full Breastfeeding and Mixed Feeding Infant - Nursyahid Siregar; Nursari Abdul Syukur; Rahmawati Wahyuni; Dwi Hendriani (Humanistic Network for Science and Technology (HNST), 2018)
Newborn infants immune systems are immature and inadequate at birth. Infants have limited abilities to infectious challenges to respond effectively and quickly, which explain infants ongoing susceptibility to infections. Passive immunity is provided for infants through IgA and other antimicrobial peptides in breast milk, particularly colostrum. The purpose of this study is to determine the differences between the levels of secretory immunoglobulin A from faeces of full breastfeeding and mixed feeding infants. Design of this study was pre-test and post-test design. The sample size was 38 neonates in community health center work areas, selected by consecutive sampling. The level of secretory IgA was measured by ELISA method, then analyzed using t-test. The results showed that no significant differences levels of secretory IgA on 0 day from faeces of full breastfeeding and mixed feeding (p-value=0.141), the levels of secretory IgA on 28 days was higher in infants of full breastfeeding than mixed feeding (p-value=0.000), delta levels of secretory IgA was higher full breastfeeding infants than mixed feeding (p=0.000). Levels of secretory immunoglobulin A of full breastfeeding infants faeces was higher than mixed feeding infants. Keywords: Secretory immunoglobulin A, Full breastfeeding, Mixed feeding